A significant role of sarcoplasmic reticulum in cardiac contraction of a basal vertebrate, the river lamprey (Lampetra fluviatilis). (4th September 2012) - Vornanen, M.; Haverinen, J.
Abstract Aim Cardiac contraction and relaxation are mediated by rapidly changing calcium concentration around the myofibrils. In comparison with endotherms, ectothermic hearts are more strongly dependent on extracellular calcium for contraction suggesting this trait might represent the primitive vertebrate mode of cardiac activation. This study tests the hypothesis that intracellular calcium stores play a minor role in cardiac excitation–contraction coupling of a basal vertebrate, the lamprey (Lampetra fluviatilis). Methods Contribution of sarcoplasmic reticulum to cardiac calcium management was examined by measuring the ryanodine sensitivity of contraction, determining the number of cardiac ryanodine receptors and their calcium sensitivity, assessing the size of sarcoplasmic reticulum calcium stores in enzymatically isolated cardiac myocytes and qualitative electron microscopic observations of sarcoplasmic reticulum in cardiac muscle. Results An extensive network of nonjunctional sarcoplasmic reticulum around myofibrils and numerous junctional sarcoplasmic reticulum couplings at the periphery of the myocytes was present in atrial and ventricular muscle of the lamprey heart. High numbers of ryanodine receptors were present in atrial (0.16 ± 0.04 nmol mg−1 prot) and ventricular membranes (0.27 ± 0.03) (P < 0.01), and 10 μm ryanodine inhibited large part of contraction force in atrial (37.8 ± 5.7%) and ventricular (49.2 ± 6.5%) muscle. Conclusion Sarcoplasmic reticulum is well developed in the lamprey heart and plays a significant role in cardiac calcium management. This suggests that in the common ancestor of vertebrates, cardiac excitation–contraction coupling could have been fairly strongly dependent on sarcoplasmic reticulum calcium stores. Functionally, this trait might be associated with high cardiac output and active predatory lifestyle of the lamprey.